Exploring Narrative Inquiry in Education: Personal and Social Learning Transformation - Alimin Alimin; Safiullah Aziz; Hunaidah Hunaidah (International Journal of Educational Narratives, 2026)
Background. Narrative inquiry has gained increasing attention in educational research as a methodological approach that captures lived experiences and meaning-making processes. However, its role in facilitating both personal and social learning transformation remains underexplored in systematic empirical studies, particularly those integrating qualitative depth with measurable outcomes. Purpose. This study aims to investigate how narrative inquiry contributes to transformative learning by examining the interplay between individual reflection and social interaction within a faculty of education context.   Method. Grounded in a constructivist-interpretivist paradigm, this research employed a qualitative narrative inquiry design involving twenty-four participants (18 undergraduate students and 6 teacher-educators) at a public university. Results. The findings reveal that narrative inquiry fosters transformative learning through three interconnected processes: reflexive self-reconstruction, empathetic engagement with others’ experiences, and the co-construction of shared meanings. Conclusion. Narrative inquiry serves as a pedagogical catalyst for personal and social transformation, rather than a merely descriptive method. The study’s novelty lies in providing empirical evidence that narrative engagement functions as an active developmental mechanism where personal reflection and social growth are mutually reinforcing. Ultimately, this approach humanizes educational practices by bridging the gap between individual biography and professional trajectory.